Faith Growing in Action:: Implications of John Locke's Tabula Rasa Concept and Ecological Education for HKBP Sunday School Children - Manalu, Musdodi Frans Jaswin (PEADA': Jurnal Pendidikan Kristen, 2024)
This study explores applying John Locke's concept of tabula rasa and Susan Power Bratton's Eco-Dimensionality theory within the context of Sunday school education at the Huria Kristen Batak Protestan (HKBP) Church. It investigates how these theories influence children's teaching and understanding of ecological responsibilities. The research employs a descriptive qualitative approach, focusing on how the HKBP Church integrates ecological teachings into its Sunday school curriculum and activities. The findings suggest that while the HKBP Church acknowledges environmental issues in its doctrines, implementing these principles is still nascent. The study highlights the importance of adapting educational content to foster ecological awareness, utilizing the tabula rasa concept to develop curricula that shape children's environmental attitudes and behaviors. It also underscores the role of interactive learning methods and evaluations to enhance children's understanding and actions towards environmental sustainability. By incorporating these educational strategies into the HKBP Sunday School Handbook, the church aims to cultivate a holistic environmental consciousness among its young members, aligned with biblical stewardship and ecological responsibility teachings.